PEMBERIAN PENGETAHUAN DAN PRAKTEK EGG ROLL TEPUNG UWI UNGU DISUBSTITUSI DENGAN IKAN LELE UNTUK PENINGKATAN PROTEIN DI PONDOK RUMAH SAJADA, WIROKRAMAN, GODEAN, SLEMAN, YOGYAKARTA - Siti Tamaroh; Yuli Perwita Sari; Wisnu Adi Yulianto (Universitas Muhammadiyah Mataram, 2024)
Rumah Sajada Orphanage and Islamic Boarding School for Orphans and Dhuafa' is a place of learning for students to improve their religious and general knowledge which will be applied in their lives and in society. Education prioritizes instilling the basic values of the Koran and Sunnah of the Prophet Muhammad. Santri are guided to have an independent nature and be able to entrepreneurship as a provision for life in society. Soft skills are given early to increase independence and self-confidence. The problem is that in Pondok Sajada there is production of cultivated catfish which has not been utilized optimally in its processing and is only sold in fresh form. The processing alternative offered in Community Service activities is making egg roll products. Egg roll is a dry food that can be stored for a long time. The addition of catfish aims to innovate fish-based preparations and utilize the catfish harvest at Rumah Sajada. The resulting egg roll contains a very useful protein component. The use of purple yam is a form of food diversification based on local ingredients. Purple yam has quite complete nutritional levels. Purple yam contains anthocyanin which has the potential to act as a natural antioxidant. Community service activities provide knowledge and practice of processing catfish egg rolls which are rich in protein and have antioxidant activity derived from purple yam. This community service activity will provide additional useful knowledge for the students at Rumah Sajada to prepare them for independence after undertaking education. Equipment assistance in the form of a set of tools for making egg rolls is useful for implementing practice to improve students' skills in making egg rolls.